Sosialisasi Anti Perundungan dan Anti Kekerasan Seksual di SMP dan SMA Purwareja Klampok, Kabupaten Banjarnegara - Suwarni, Titi; Krisnanda, Isro Wahyu; Wibowo, Nur Hidayat Mashuri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Talking about bullying and sexual violence for students should be a priority for all parties. Currently, bullying and sexual violence have become a hot topic of discussion in the world of education. The existence of cases of bullying and sexual violence that occur in schools makes us very concerned, of course this must be a big concern for all parties, how do we find out the causes and then find the best solution so that there are no more cases of bullying and sexual violence in students. Sexual violence refers to actions that involve the coercion of sexual harassment against someone. Bullying, or often called bullying, is an aggressive and repeated act committed by one individual or a group of individuals against act committed by one individual or a group of individuals against another, with the aim of hurting and degrading, or intimidating the victim. Sexual violence and bullying often occur in the school environment. Children and adolescents are vulnerable to being victims and perpetrators of these acts. Sexual violence and bullying in schools have a serious impact on victims. They can experience psychological trauma, anxiety disorders, depression, decreased academic performance, and even a high risk of suicide. Prevention of sexual violence and bullying in schools involves the cooperation of all school parties, namely between students, teachers, parents, school staff, and the community in the school. Prevention of sexual violence and bullying in schools is a shared responsibility to protect children and adolescents from physical and psychological harm. With the right education, social support and proactive measures, we can create a safe, inclusive and supportive school environment for all learners. It is also expected to increase the spirit of learning and improve students' achievement